2022
DOI: 10.1109/access.2022.3150930
|View full text |Cite
|
Sign up to set email alerts
|

How Does Proximity Affect the Dual Innovation of Alliance Partner? The Role of Knowledge Coupling

Abstract: Recent work on alliance partner selection focuses on the relationship between partner features and alliance performance, while ignoring the influence mechanism of alliance partner features on different innovation types of firms. In this paper, based on proximity perspective, the influence mechanism model of alliance partner features on firms' dual innovation is constructed. Analyzing questionnaires and patent data of high-tech firms, it is found that (1) Technological proximity (TP) has a positive impact on fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Fourth, results also prove the mediating effect of collaboration network stickiness between similarity and collaborative performance, while its mediating role between complementarity and collaborative performance has not been confirmed. For one thing, Sticky collaboration enhances knowledge coupling between partners, facilitating interaction, interconnection and dependence between both firms' knowledge elements, which ensures successful implementation of innovation activities (Sun et al, 2022). For another, excessive heterogeneous knowledge brought by complementarity might discourage establishment of stable relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, results also prove the mediating effect of collaboration network stickiness between similarity and collaborative performance, while its mediating role between complementarity and collaborative performance has not been confirmed. For one thing, Sticky collaboration enhances knowledge coupling between partners, facilitating interaction, interconnection and dependence between both firms' knowledge elements, which ensures successful implementation of innovation activities (Sun et al, 2022). For another, excessive heterogeneous knowledge brought by complementarity might discourage establishment of stable relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of geographical proximity can promote better face-to-face communication between the two sides, promote the transmission of knowledge and technology, reduce the negative effect caused by information asymmetry, and help enterprises effectively use the scientific research advantages of scientific research organizations to promote innovation [16]. However, when the geographical location between enterprises and scientific research organizations is too concentrated, the external innovation environment of the two is closed, thereby reducing the heterogeneity of technological innovation, causing fatigue and negativity of cooperative relations between enterprises and scientific research organizations, and hindering the effective development of interactive learning and innovation activities [17]. In addition, appropriately improving the proximity of technology can promote the continuous interaction of knowledge and technology between the two sides, and the research results of scientific research organizations are always consistent with the innovation needs of enterprises, which can reduce the communication barriers between the two sides, improve communication efficiency, enhance the understanding and absorption ability of enterprises to invisible knowledge and technology, and thus promote the transformation of scientific research results [18].…”
Section: ) Between Enterprises and Scientific Research Organizationsmentioning
confidence: 99%
“…From this perspective, the degree of KC in the form of AI is the key factor [32], and the performance of technological innovation activities is inevitably affected by this factor. Although some studies have found that KC is a key factor in technological innovation and have shown that the coupling between different knowledge fields can lead to new knowledge creation and, thus, innovation [33][34][35], most of the existing studies only discuss its role in technological innovation [36][37][38], and it is rare to explore the mechanism of KC from the perspective of different interaction intensities under different collaborative relationships.…”
Section: Introductionmentioning
confidence: 99%